Measuring global temperatures : - Strangeways, Ian (Cambridge University Press, 2010)
"Temperature is probably the most influential of all climatic variables. Our only direct, quantitative knowledge of global temperatures comes from instruments operated over the last 150 or so years. Yet as crucial and as central as these data are to our understanding of the climate, they are largely taken for granted, even by many of those using them. Measuring Global Temperatures will fill this gap by explaining how global temperatures are measured, how the data is analysed, what the potential errors are, and what needs to be done to improve temperature measurement in the future. The book is of great interest to all meteorologists, climatologists, and hydrologists, and especially those concerned with climate change and global warming. It is written in accessible language with little mathematics, and so will appeal to students and amateur meteorologists with a strong interest in weather and climate"--Provided by publisher.